Analysis of risk factors for the incidence of pulmonary tuberculosis in Tebing Tinggi Community Health Center: A cross-sectional study - Dwi Sartika; Ali Harokan; Lilis Suryani (Lentera Perawat, 2025)
Background Pulmonary tuberculosis (TB) remains a persistent public health concern in Indonesia, driven by a complex interplay of individual and environmental risk factors. Understanding these determinants is crucial to enhance disease control strategies at the community level. Objective This study aimed to analyze the risk factors associated with the incidence of pulmonary tuberculosis in the working area of Tebing Tinggi Public Health Center, Empat Lawang. Methods A quantitative cross-sectional study was conducted involving 76 respondents selected from 321 suspected TB patients using purposive sampling. Data were collected using structured questionnaires. Bivariate analysis was performed using the Chi-Square test, and multivariate analysis was conducted using logistic regression to determine the dominant risk factors. Results Bivariate analysis showed that age (p = 0.04) and household contact (p = 0.00) were significantly associated with the incidence of pulmonary TB, while gender, knowledge, housing density, and ventilation were not (p > 0.05). Multivariate analysis revealed that household contact was the most dominant factor influencing TB incidence. Conclusion Household contact and older age were significantly associated with pulmonary tuberculosis incidence. Targeted interventions such as household contact tracing and focused health education for older populations are essential to reduce transmission and improve TB control at the community level.